ANALYSIS OF HIGH SCHOOL STUDENTS’ NEEDS FOR INSTRUCTIONAL MEDIA MADE USING ADOBE FLASH CS6 ABOUT VIRUS MATERIAL - Tria Febrianti Pangestu; Ristiono Ristiono; Novia Sari Prihartini (Universitas Negeri Padang, 2021)
Virus material is material that is difficult for students to understand, so it requires media that can clarify virus material. The solution to this problem is to create interactive learning media. This study aims to see the needs of students for interactive learning media based on Adobe Flash CS6 about virus material for class X students of SMAN 6 Bataghari. This type of research is descriptive quantitative. The method used to collect data was done through distributing online questionnaires to class X students and interviewing one biology teacher. The results of the study revealed that students had difficulties in understanding biology learning on viral material due to the abstract material and the lack of learning media that attracted students' attention and interest in learning. In addition, students considered the media used by the previous teacher to be monotonous and less attractive. Therefore, we need an interactive learning media that can help students to understand the learning material.